Thomas Aquinas: Integrating Faith and Reason in the Catholic School - Doyle, Dennis M. (Catholic Education: A Journal of Inquiry and Practice, 2007)
The Second Vatican Council, social upheaval, and quickly changing cultural norms were a part of the fabric of life in the 1960s. Values and beliefs held firmly for generations were called into question. Faith, once solid, appeared to some Catholics to turn fluid and doubtful. Though now well over seven centuries old, the work of Thomas Aquinas can itself be understood and appreciated as a response to the demands of philosophical challenges that threatened to make things fall apart. By his fitting together of faith and reason, Aquinas’ intellectual approach can serve as a inspiration for educators, especially those at the high school level.